2021
DOI: 10.48084/etasr.4607
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Transmitting Antennas for Solar Power Satellite Systems

Abstract: This study attempts to identify, design, and evaluate transmitting antennas for Solar Power Satellite (SPS) systems. The design approach aimed at meeting the SPS operational requirements at ISM bands, namely 2.4-2.5GHz for the NASA and 5.725-5.875GHz for the JAXA models. The primary attributes of SPS antennas for transmitting Beamed High-Power Microwaves (BHPMs) are high power handling capability, efficiency, and directivity with narrow beamwidth and lower sidelobe levels. Using a planar end-fed 20×20 SWA modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The huge demand of Q, V bands for satellite communications stimulated the design of millimeter wave applications. The low noise amplifier is a critical and essential component of millimeter wave applications of satellite communications [1][2][3]. BICMOS and MESFET technologies were able to support the MMIC LNA design only up to RF micro meter level (3 to 30 GHz) [4], but the MMIC LNA design at the milli meter level (30 GHz -300 GHz) is supported only by HEMT technologies [5].…”
Section: Introductionmentioning
confidence: 99%
“…The huge demand of Q, V bands for satellite communications stimulated the design of millimeter wave applications. The low noise amplifier is a critical and essential component of millimeter wave applications of satellite communications [1][2][3]. BICMOS and MESFET technologies were able to support the MMIC LNA design only up to RF micro meter level (3 to 30 GHz) [4], but the MMIC LNA design at the milli meter level (30 GHz -300 GHz) is supported only by HEMT technologies [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, electron-impact ionization has been used to measure a detailed ionization spectrum and cross-sections using various methods [4]. Plasma is important in nuclear physics because many studies showed that it can take various shapes, including nonequilibrium plasma that is used to change the characteristics of the surface [5,6]. The characteristics of non-equilibrium plasmas are known through the ionization of atoms and molecules by electron impact, which has great practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, EII is important to model astrophysical systems including nonthermal distributions [4]. Determining the spatial distribution of hot electrons in plasma is very crucial as they affect radiation production, energy balance, and plasma dynamics [5,6]. These electrons may cause considerable energy losses and negatively impact the plasma's stability and control.…”
Section: Introductionmentioning
confidence: 99%